The effect of time trial cycling position on physiological and aerodynamic variables - Fintelman, D. M.; Sterling, M.; Hemida, H.; Li, F.-X. (Journal of Sports Sciences, 2015)
To reduce aerodynamic resistance cyclists lower their torso angle, concurrently reducing Peak Power Output (PPO). However, realistic torso angle changes in the range used by time trial cyclists have not yet been examined. Therefore the aim of this study was to investigate the effect of torso angle on physiological parameters and frontal area in different commonly used time trial positions. Nineteen well-trained male cyclists performed incremental tests on a cycle ergometer at five different torso angles: their preferred torso angle and at 0, 8, 16 and 24°. Oxygen uptake, carbon dioxide expiration, minute ventilation, gross efficiency, PPO, heart rate, cadence and frontal area were recorded. The frontal area provides an estimate of the aerodynamic drag. Overall, results showed that lower torso angles attenuated performance. Maximal values of all variables, attained in the incremental test, decreased with lower torso angles (P < 0.001). The 0° torso angle position significantly affected the metabolic and physiological variables compared to all other investigated positions. At constant submaximal intensities of 60, 70 and 80% PPO, all variables significantly increased with increasing intensity (P < 0.0001) and decreasing torso angle (P < 0.005). This study shows that for trained cyclists there should be a trade-off between the aerodynamic drag and physiological functioning.